Upregulation of matrix synthesis in chondrocyte-seeded agarose following sustained bi-axial cyclic loading (Clinics, 2012)
OBJECTIVES: The promotion of extracellular matrix synthesis by chondrocytes is a requisite part of an effective cartilage tissue engineering strategy. The aim of this in vitro study was to determine the effect of bi-axial cyclic mechanical loading on cell proliferation and the synthesis of glycosaminoglycans by chondrocytes in threedimensional cultures. METHOD: A strain comprising 10% direct compression and 1% compressive shear was applied to bovine chondrocytes seeded in an agarose gel during two 12-hour conditioning periods separated by a 12-hour resting period. RESULTS: The bi-axial-loaded chondrocytes demonstrated a significant increase in glycosaminoglycan synthesis compared with samples exposed to uni-axial or no loading over the same period (p